2021
DOI: 10.32832/jm-uika.v12i2.3946
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Liquidity, Leverage and Bank’s Size on Bank’s Profitability of Indonesian Listed Bank

Abstract: <p><em>The purpose of this study is to determine the impact of liquidity, leverage and bank size on profitability in Indonesian conventional banking sector</em><em> as the influencer of economic movements in this country</em><em>. This study employed the total of  29 commercial banks listed on Indonesia Stock Exchange during the period of 2010-2019. There are total of 290 observations made in the study. The dependent variable used in this study is bank’s profitability measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 7 publications
3
8
0
5
Order By: Relevance
“…Present study showed that the inflation rate has no positive impact on productivity. Few studies have proved the similar result like Bhattarai [40], ] Lestaria et al [27], Sukmana R., Febriyati [55], inflation on of determinates of profitability of bank that with induce high volume of bank's loan which is affected bank profitability. Table 7 showed that GDP growth rate has a positive impact on banks profitability [56].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Present study showed that the inflation rate has no positive impact on productivity. Few studies have proved the similar result like Bhattarai [40], ] Lestaria et al [27], Sukmana R., Febriyati [55], inflation on of determinates of profitability of bank that with induce high volume of bank's loan which is affected bank profitability. Table 7 showed that GDP growth rate has a positive impact on banks profitability [56].…”
Section: Discussionmentioning
confidence: 76%
“…Moudud-Ul-Huq, Halim and Biswas [26] conducted a study on completion and profitability of banks from Middle East and North African countries during 2011-2017 found a significant negative impact of completion on bank's profitability. Lestaria, et al [27] found that there is a negative impact of liquidity and leverage on profitability (ROE) and positive impact of bank size on profitability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Profitability measures management efficiency in using organizational resources to add business value. Profitability can be considered a relative term to measure profit and its relationship with other elements directly affecting company profits (Lestari et al, 2021).…”
Section: Profitabilitymentioning
confidence: 99%
“…Return on assets (ROA) is one of the indicators of profitability used to measure the efficiency of a company in generating profits from the management of company assets. ROA shows the company's profit relative to the total assets owned, calculated by net profit to total assets (Lestari et al, 2021). ROA as indicators for measuring bank profitability and measured by the following formula: ROA = Many studies discuss the relationship between bank liquidity and profitability (Moussa & Boubaker, 2020).…”
Section: Profitabilitymentioning
confidence: 99%
See 1 more Smart Citation